Examining the effectiveness and implementation of patient treatment decision‐aid tools for men with localised prostate cancer: A systematic review. Issue 4 (27th January 2023) - Todio, Elizabeth; Sharp, Jessica; Morrow, April; Taylor, Natalie; Schofield, Penelope; Mazariego, Carolyn
Abstract: Objective: Men diagnosed with localised prostate cancer (LPC) often face a difficult process deciding on a treatment choice that suits their personal preferences. This systematic review examines the impact of patient treatment decision‐aids (DAs) on decisional outcomes and treatment choice for men diagnosed with LPC. Our secondary aim was to examine how DAs have been implemented into routine clinical practice. Methods: A systematic search was conducted up to June 2022 using the following databases: Medline, Embase, PsycINFO, CINAHL, Cochrane, Scopus, and Web of Science. Articles were included if they evaluated the effectiveness of treatment DAs for LPC patients on various decisional outcomes and treatment choice. The Mixed‐Method Appraisal Tool was used to assess methodological quality and risk of bias. Data on implementation outcomes were also extracted if reported. Results: Twenty‐four articles were included for the analysis (seven non‐randomised studies, 16 randomised control trials, and one qualitative study). Results showed DAs have the potential to improve patient knowledge but revealed no effects on decisional regret or preparedness in decision‐making. Due to the variability in methodology among studies, results varied widely for treatment choice, decision‐making involvement, decisional conflict, and treatment decision satisfaction. At least one implementation outcome was reported in 11 of the included studies, with the most commonly assessed outcomes being acceptability and appropriateness. Conclusions: While DAs appear to improve knowledge, further qualitative evaluations and standardised assessments are needed to better understand men's experiences using DAs and to determine advantages and optimal ways to implement DAs into the treatment decision‐making pathway.